2014
DOI: 10.4102/ojvr.v81i1.836
|View full text |Cite
|
Sign up to set email alerts
|

First report of a mixed infection of <i>Trichinella nelsoni</i> and <i>Trichinella</i> T8 in a leopard (<i>Panthera pardus</i>) from the Greater Kruger National Park, South Africa

Abstract: At least three Trichinella species, namely Trichinella nelsoni, Trichinella britovi and Trichinella zimbabwensis, and one genotype (Trichinella T8), have been isolated from sylvatic carnivores on the African continent. With the exception of T. britovi, the other species are known to circulate in wildlife of the Kruger National Park (KNP), South Africa, and KNP neighbouring game reserves (collectively known as the greater KNP area). Lions (Panthera leo) and spotted hyenas (Crocuta crocuta) appear to be the most… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(21 citation statements)
references
References 25 publications
2
19
0
Order By: Relevance
“…Till date, infection of T. nelsoni from Tanzania (Pozio et al, 1997) and T. britovi from Iran (Mowlavi et al, 2009) in leopards has been reported. A mixed infection of T. nelsoni and T8 genotype in leopard has also been reported from Greater Kruger National Park, South Africa (La Grange et al, 2014).…”
Section: Resultsmentioning
confidence: 83%
“…Till date, infection of T. nelsoni from Tanzania (Pozio et al, 1997) and T. britovi from Iran (Mowlavi et al, 2009) in leopards has been reported. A mixed infection of T. nelsoni and T8 genotype in leopard has also been reported from Greater Kruger National Park, South Africa (La Grange et al, 2014).…”
Section: Resultsmentioning
confidence: 83%
“…In the GKNP, only a single leopard (1/7, 14%) tested positive for T. nelsoni [54] and the same species has previously been isolated from leopards in Kenya [66] and Tanzania [67]. La Grange et al [38] described a mixed infection of T. nelsoni and Trichinella T8 in a leopard from the GKNP and based on the dietary habits of the species [4,20,42,94], we hypothesise that other small mammalian carnivores may serve as an important source of infection to these animals in the GKNP. Similar to T. nelsoni, genotype Trichinella T8 has been found in low prevalence in lions (4/98, 4%), hyaenas (1/26, 3.8%) [43,54,76] and leopards (1/7, 14%) from the GKNP [38,54].…”
Section: Resultsmentioning
confidence: 97%
“…Trichinella species reported in the GKNP From the beginning of Trichinella surveillance studies in South Africa in 1964 to the end of 2016, at least two species and one genotype have been confirmed across six mammalian and two reptilian hosts from the GKNP [38,40,43,54,79]. Trichinella-like infections have additionally been reported in six other mammalian hosts, but species confirmation of the parasite was not possible [43,54,100,101].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Most previous research on trichinellosis in Africa focused on isolating Trichinella from wildlife [713], and it was long believed that in Africa, Trichinella infection essentially affects wild carnivores [14] and that pigs are not infected with Trichinella in East Africa. Outbreaks of human trichinellosis in Africa date back several decades and were documented in Egypt [15], Northwest Ethiopia [16,17], Kenya [18] and Tanzania [19].…”
Section: Introductionmentioning
confidence: 99%